Peningkatan Hasil Belajar Siswa Pada Materi Bahasa Indonesia Melalui Penerapan Model Pembelajaran Inside Outside Circle (Ioc) Di Kelas III MI - Sisi, La; Kasmawati; Sabania (Student Journal of Early Childhood Education, 2024)
The aim of this research is to increase student learning outcomes in Indonesian language material through the application of the Inside Outside Circle (IOC) learning model in third Class MI Al-Fath Kendari. The subjects of this research were teachers and students of class III MI Al-Fath Kendari who were registered in the even semester of the 2022/2023 academic year with a total of 20 students. Implementation of the action follows the following classroom action research procedures; 1) planning; 2) implementation of actions and observations; 3) evaluation; 4) reflection. This research was carried out in two cycles. This type of research is classroom action research. The data in this research are qualitative data and quantitative data. Qualitative data was taken using observation sheets, while quantitative data was obtained through cycle tests. The results show that the IOC learning model increases learning outcomes in Indonesian language material by 69.25 in cycle I to 78.25 in cycle II. This is because this model involves children in learning to work together which aims to train students to learn independently and learn to speak, convey information to others.